Comparison of different gasoline alternative fuels in terms of laminar burning velocity at increased gas temperatures and exhaust gas recirculation rates - Knorsch, Tobias; Zackel, Andreas; Mamaikin, Dmitrii; Zigan, Lars; Wensing, Michael (Energy & Fuels, 2014)
The butanol isomers n-butanol and isobutanol as well as ethanol are among the biofuels most likely to be used for engine combustion and are likely to become more relevant as surrogate fuels or blend components in the future. To use the potentials of alternative fuels, the combustion mechanisms and, thus, burning behavior should be known. A key parameter for flame kinetic studies and combustion simulation is the laminar burning velocity. However, reproducible measurements of flame speeds of gasified liquid fuels are difficult. To reduce the scattering of experimental results to acceptable levels, there is a common research interest of several European institutes using so-called heat flux burners. In this work, a self-designed liquid fuel evaporation system has been combined with a precise droplet generator, which allows for measurements of adiabatic laminar burning velocity at elevated gas temperatures. The one-dimensional (1D) flame appears very stable, even close to its flammability limits. The boundary conditions are chosen to model exhaust gas recirculation (EGR) with different temperatures and compositions of the mixtures. The measurement data are compared to the corresponding results of other research groups, and the uncertainty of the burning velocity is estimated. © 2014 American Chemical Society.
Created from Fastlane, Scopus look-up